Value of Aspect Differences Towards Theory of Planned Behavior Between Hospital Personnels of a Private Hospital in Mataram - Nadia Sutanto; Made Aswina Putra (ANIMA Indonesian Psychological Journal, 2019)
Medical staffs are considered to be people who should be able to set an example to the public, concerning the way life should be lived. The design of this research was that of a comparative study model, which compared aspects of the Theory of Planned Behavior from three groups of medical staff subjects. The research was aimed at providing a basic picture of the obesity of the medical staff in a private hospital in Mataram, West Nusa Tenggara, Indonesia. Besides this, it also searched for differences in perceptions, based upon the Theory of Planned Behavior. The research results indicated that, of the aspects of Theory of Planned Behavior, it was only those of Intention, Subjective Norms, and Attitudes Toward Behavior, which showed any differences between the subject groups, that is, the groups of those suffering obesity demonstrated an intention to perform, and a positive attitude towards, behavior aimed at reducing bodily weight.